Dynamic Linkages among Foreign Exchange, Stock, and Commodity Markets in Northeast Asian Countries: Effects from Two Recent Crises - Yang, Lu; Hamori, Shigeyuki (Journal of Reviews on Global Economics, 2013)
This paper investigates the interaction among the foreign exchange, stock, and commodity markets of Northeast Asian countries according to the cross-correlation function (CCF) approach. We analyze the impact of the global financial crisis and the European sovereign crisis on the financial market interactions of Japan, South Korea, and Taiwan. The empirical results show that financial markets in different countries show different causality relationships. While interactions in both mean and variance are relatively strong in Japanese financial markets, they are relatively weak in Korean markets. We cannot find any financial market interactions in Taiwan.